Pros and cons of circumcision: an evidence-based overview. (September 2016) - Friedman, B.; Khoury, J.; Petersiel, N.; Yahalomi, T.; Paul, M.; Neuberger, A.
Abstract: Based on three large randomized controlled trials (RCTs) conducted in Africa, it can clearly be stated that circumcision lowers the risk of infection with the human immunodeficiency virus (HIV) and some sexually transmitted infections (STIs) among males in settings of high HIV and STI endemicity. Similar effects on STI risk may exist for females, although this may result from an indirect effect of decreasing risk of infection among male partners. It is unknown whether circumcision prevents HIV acquisition in men who have sex with men (MSM), although there might be a protective effect for men who engage mainly in insertive anal intercourse. When the effects of adult circumcision on sexual function and satisfaction of men are examined, high-quality evidence strongly supports lack of harm. Whether circumcision alters sexual satisfaction of female partners is not known as fewer and smaller studies reported conflicting results. Circumcision rarely causes serious complications if practiced by trained practitioners, in a sterile setting, and with a proper follow-up. These conclusions are limited by the lack of high-quality data from areas outside of Africa. RCTs have not been conducted to assess the effects of circumcising infants or MSM. Circumcision has well-proven benefits for people residing in areas with high prevalence of STIs, including HIV, and is not unethical for those who choose to be circumcised or have their children circumcised on religious, social, or cultural grounds. For many others, a definite pro or con recommendation, based on a risk-benefit ratio, cannot be made.